Dairy cattle judging fundamentals - Maddox, Bill.; Creative Educational Video, Inc. (Lubbock, TX : CEV Multimedia, 1998)
Illustrates the fundamentals of judging dairy cattle. Includes review sections.
Fakulti Perubatan Veterinar.
Narration, Bill Maddox.
Keywords: Dairy cattle -- Judging